PENGETAHUAN DAN SIKAP IBU MENYUSUI TENTANG PEMBERIAN ASI EKSLUSIF DI WILAYAH KERJA PUSKESMAS DATUK BANDAR KOTA TANJUNG BALAI TAHUN 2018 - IRNA SARTIKA; MENI FUZI ASTUTI TANJUNG (JURNAL ILMIAH SIMANTEK, 2019)
Breast milk is a living fluid that God created specifically for infants, breast milk is a living fluid because it contains white blood cells, antibodies, enzymes, hormones, and proteins suitable for infants necessary for growth, development, and survival. Exclusive breastfeeding is that infants receive only breast milk from mothers or caregivers who are asked to provide breast milk of the mother, without the addition of liquids or solids, except the syrup containing vitamins, mineral supplements or medicine.This study was a descriptive study that aims to describe quantitative Knowledge and Attitudes Mother about Exclusive Breastfeeding. Data collection tools used in this study was a questionnaire, the number of samples are 46 mother.The results showed that the level of knowledge both as many as 26 people (56.6%), insufficient knowledge of 18 people (39.1%) and lack of knowledge as much as 2 people (24.2%). Good attitude many as 12 people (26.1%), had an attitude quite as many as 21 people (45.7%) and respondents who have less attitude as many as 13 people (28.3%).